A dietary switch promotes sensory neuron–dependent cancer-associated cachexia - Michael Cross; Stefan Kotschi; Warren Wu; Fedra Luciano-Mateo; Young-Yon Kwon; Ezequiel Dantas; Taha Niazi; Shijia Chen; Ali Rashidfarrokhi; Ray Pillai; Jack Sanford; Jeshua Kim; et al. (Science, 2026)
Sickness behaviors are common in cancer-associated cachexia and affect up to half of lung cancer patients. We demonstrate that among the most common cancer mutations, loss of liver kinase B1 ( Lkb1 ) promotes the development of cachexia in preclinical models of lung cancer. In an effort to improve caloric intake with an obesogenic high-fat diet, we paradoxically observed worsened cachexia-associated sickness. We found that local production of prostaglandin E2 (PGE 2 ), rather than circulating factors, promotes sickness and that genetic, dietary, and pharmacological inhibition of tumor-derived PGE 2 suppresses sickness and cachexia. Notably, we demonstrate that lung sensory neuron abrogation prevents PGE 2 -dependent cachexia. Our study establishes localized tumor-derived signals to sensory neurons, rather than circulating factors, as drivers of cachexia and highlights a previously unknown role of the peripheral nervous system in cancer cachexia.